Behavioural approach as the basis of traditional market redevelopment strategies - Assyifa, Ajeng Regita; Asharhani, Imaniar Sofia; Kusuma, Adriyan (Department of Architecture Faculty of Engineering Universitas Indonesia, 2025)
This design study focuses on the redevelopment of the Kebayoran Lama traditional market using a behavioural approach. Traditional markets hold an important role in the social, economic, and cultural life of urban communities, functioning not only as centres of trade but also as spaces for interaction that shape the city's character. However, rapid urban development often creates challenges for traditional markets, reducing their competitiveness against modern shopping centres. The study began with direct observation and behavioural mapping activities at the Kebayoran Lama traditional market to understand how traders and visitors interact with the space. Findings show the current layout does not support user needs due to irregular commodity placement, limited circulation, inactive stalls, and trading activities spilling outside the building. This research proposes strategies to restructure the market into a more adaptive, inclusive, and sustainable space. The design sought to reprogram the spatial boundaries to identify a setting for particular behaviour, improve wayfinding to create clearer spatial cognition, and develop sensorial experience to enhance environmental perception. These redevelopment strategies demonstrate an integrated framework of behaviour approach to functionally efficient, cognitively legible, and socially engaging spaces, strengthening the market's role as a vital centre of economic and social activities for the community.